2009
DOI: 10.1063/1.3141818
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous photoresponse of GaN x-ray Schottky detectors

Abstract: GaN based materials are believed to be very stable materials, in particular, under irradiation by high energy photons such as x rays. We have studied x-ray detectors based on GaN Schottky diodes. Vertical Schottky diodes were fabricated based on a 20μm thick undoped GaN layer grown on a conductive GaN substrate. Their photoresponse to near UV light and to x rays was measured. While the response to near UV light was fast and linear as expected, anomalous behaviors were observed under x-ray illumination. The pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
4
25
2
Order By: Relevance
“…, and the CCE of the 12-lm device under a fluence of 10 16 cm À2 decreased from 53% to 20%. They suggested that the degradation is mainly due to an increased number of recombination/trapping centers.…”
Section: à2mentioning
confidence: 99%
See 4 more Smart Citations
“…, and the CCE of the 12-lm device under a fluence of 10 16 cm À2 decreased from 53% to 20%. They suggested that the degradation is mainly due to an increased number of recombination/trapping centers.…”
Section: à2mentioning
confidence: 99%
“…4 shows the transient characteristics after the X-ray source was switched on and off at two different power levels. 16 X-ray detection has also been performed with a p-i-n structure, 22 but despite the different structures employed, a fast transient increase or decrease (of less than 1 s) followed by a slow exponential increase or decay is seen in all the measured photocurrents. According to Duboz et al, 15 this photocurrent characteristic can be explained in terms of two currents: photovoltaic and photoconductive.…”
Section: à3mentioning
confidence: 99%
See 3 more Smart Citations